Analysis of Material and Wavelength Effects on Optical Propagation Performance in Dual Parallel Symmetric Mach-Zehnder Interferometer (DPS-MZI) Structures Using OptiBPM - Fadhilah, Nisa’ul; Ramadani, Riski; Nikmah, Afiyah; Bagoes Anargiansyah, Muhammad; Khoiro, Muhimmatul (Proceeding of International Joint Conference on UNESA, 2025)
Innovations in integrated photonic technology have increased the demand for compact and high-performance optical devices. The MZI (Mach Zender Inferferometer) is a key component, particularly the DPS-MZI structure, which offers flexibility in optical signal processing, spectral filtering, and high-precision sensing applications. This study analyses the optical characteristics and performance of DPS-MZI structures based on four waveguide core materials of Si, InGaAsP, LiNbO₃, and PMMA, at wavelengths of 532 nm, 633 nm, 850 nm, and 1550 nm. Simulations were conducted using the OptiBPM software, which employs the BPM, to evaluate optical field intensity distribution, interference patterns, and propagation losses. The results indicate that Si and InGaAsP exhibit the best propagation performance, with low power loss and sharp interference patterns, while LiNbO₃ experiences higher propagation losses despite its high electro-optic coefficient. PMMA demonstrates the lowest performance due to its low refractive index contrast, leading to significant light spreading into the cladding and high propagation losses. An increase in wavelength tends to broaden the optical mode, particularly in materials with low refractive index contrast. This study underscores the importance of selecting appropriate waveguide core materials and operating wavelengths when designing DPS-MZI-based photonic devices to ensure stable and efficient light propagation.